2017
DOI: 10.1111/roiw.12309
|View full text |Cite
|
Sign up to set email alerts
|

Energy Subsidy Reform and Poverty in Arab Countries: A Comparative CGE‐Microsimulation Analysis of Egypt and Jordan

Abstract: This study simulates the macroeconomic and distributive impacts of real proposed (by local policy makers) energy subsidy reforms in Egypt and Jordan. To do that, we develop a dynamic CGEmicrosimulation model that is able to reconcile the general equilibrium effects of the reform and the individual-and household-specific distributive effects. While the nature of the proposed reforms differs in the two countries, the study underscores the need, in both countries, for reform to generate fiscal savings to boost pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…However, the main contribution comes from the Targeted Subsidy Program with a marginal contribution of about 0.05 Gini points. This is in line with findings of Cockburn, Robichaud, and Tiberti (2018), that utilize ex-ante simulations of energy subsidy reform proposals in Egypt and Jordan (two countries that are also in the Middle East region) to show that using cash transfers to reallocate part of the freed-up resources would have a significant effect on reducing poverty in these two countries.…”
Section: Resultssupporting
confidence: 89%
“…However, the main contribution comes from the Targeted Subsidy Program with a marginal contribution of about 0.05 Gini points. This is in line with findings of Cockburn, Robichaud, and Tiberti (2018), that utilize ex-ante simulations of energy subsidy reform proposals in Egypt and Jordan (two countries that are also in the Middle East region) to show that using cash transfers to reallocate part of the freed-up resources would have a significant effect on reducing poverty in these two countries.…”
Section: Resultssupporting
confidence: 89%
“…Siddiq et al (2015) also claimed that the subsidies on imported fuels stood at about 80% of the Nigerian energy market. The complete abolishment of fuel subsidies is desirable where the additional savings can be placed on high-priority measures (Clements et al, 2007;Cockburn, Robichaud, & Tiberti, 2018;Dabla-Norris, Kochhar, Suphaphiphat, Ricka & Tsounta, 2015;IEA et al, 2010;Laderchi, 2014). The additional subsidy savings could be re-injected into the economic system using autonomous expenditures (Hamid & Rashid, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Such a reallocation stands in contrast to the direct cash assistance that was imposed under the reform, and aims at protecting the consumption level of the targeted recipients against high price levels (Cockburn et al, 2018;Cooke, Hague, Tiberti, Cockburn, & El Lahga, 2015;El-Katiri & Fattouch, 2015;Feltenstein, 2017;Feng, Hubacek, Liu, Marchán, & Vogt-Schilb, 2018;IEA et al, 2010;Laderchi, 2014). Cockburn et al (2018) found that the poverty increases due to fuel subsidy cuts in Egypt and Jordan could be offset if the saving reallocation of the cash transfer was put into practice. Besides, Siddiq, et al (2015) underlined the greatest effect of the fund transfer targeting the oil refinery sector, yet, the provision of cash assistance to poor households had a relatively fair improvement in domestic production.…”
Section: Literature Reviewmentioning
confidence: 99%
“…John Cockburn and Luca Tiberti have co-edited (with Hélène Maisonnave), no longer than a year ago, a special issue of the IJM on joint CGE (computable general equilibrium) -microsimulation modelling in developing Countries. 1 They now have a paper (Cockburn et al, 2017), forthcoming in the Review of Income and Wealth, where they present an interesting combination of macro (CGE) modelling and microsimulations in a dynamic framework. This combination of tools makes it RICHIARDI Editorial possible to map out and compare the effects of energy subsidy reforms at the macro, meso and micro (poverty) levels in two Arab Countries: Jordan and Egypt.…”
Section: Suggestions For Further Readingsmentioning
confidence: 99%